“New Wine in an Old Bottle”? – Anniversary Journalism and the Public Commemoration of the End of the War in Vietnam - Sanko, Christina (Global Media Journal - German Edition, 2016)
April 30th, 2015 marked the 40th anniversary of the end of the war in Vietnam. This article discusses the role of Vietnamese journalism in the coverage of this commemorative date as well as the history and events it is linked with. It addresses the question of how coming to terms with the past plays out in the journalistic field of an increasingly globally connected and economically continuously growing Vietnam. By means of qualitative content analysis and expert interviews with Vietnamese media professionals the paper characterizes the nature of anniversary journalism on this particular event and elaborates on its meaning for the construction of cultural memory in Vietnam. In that context, it also touches upon transnational relations with and controversies of remembrance in Vietnamese diasporic communities. The study found that anniversary journalism in Vietnam goes beyond the mere coverage of a single commemorated day along state ideological lines and constitutes part of a larger context of cultural memory in Vietnam and the diaspora. It is itself subject to change over time and of tensions between state, economic, professional and personal interests in a vastly changing, but still state-controlled media environment. Such tensions can result in ambiguities, vagueness and the coexistence of a variety of narratives in the reporting. Despite slight liberation tendencies, however, anniversary journalism on the contentious meaning of April 30th does not represent a transnational forum for negotiating the past in Vietnam and its diaspora.